Eurocene and the Myth of Development in Helon Habila’s Oil on Water and Chimeka Garricks’ Tomorrow Died Yesterday - Alvie Dieu-Mercy Mouzita (ELS Journal on Interdisciplinary Studies in Humanities, 2026)
This paper is an in-depth analysis of Helon Habila’s Oil on Water and Chimeka Garricks’ Tomorrow Died Yesterday. The study aims at showing the paradox of oil wealth in the Niger Delta. It argues that Eurocene and the myth of development intersect, in both novels, as an awful ideology of western corporations to get huge profit from exploitation, under the martial control of environment. Using a postcolonial ecocritical framework and qualitative textual analysis, the paper explores three major findings. First, Eurocene is not a distant epoch, but a current reality that links capitalism, ecological destruction, and social oppression. Second, the myth of development is rhetoric device to deceive local populations and legitimize ecological exploitation while enriching corrupt elites and western companies. Third, instead of prosperity, oil activities leave local communities with oil spills, gas flares, health hazards, the collapse of traditional livelihoods, worsening living conditions, and the displacement of entire communities. By dramatizing the social, cultural, and ecological costs of oil exploitation, Habila and Garricks contribute to a literary tradition that challenges oppression. The study concludes that African literature functions as a space of resistance, exposing the destructive colonial legacies, advocating, therefore, for ecological justice and for more equitable visions of development.